2014
DOI: 10.1590/s1413-35552012005000145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on isometric muscle strength, fat-free mass and electromyographic signal power of the upper and lower limbs in women

Abstract: Background Aging is a multifactorial process that leads to changes in the quantity and quality of skeletal muscle and contributes to decreased levels of muscle strength. Objective This study sought to investigate whether the isometric muscle strength, fat-free mass (FFM) and power of the electromyographic (EMG) signal of the upper and lower limbs of women are similarly affected by aging. Method The sample consisted of 63 women, who were subdivided into three groups (young (YO) n=33, 24.7±3.5 years; middle age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
21
0
2
Order By: Relevance
“…Similar to previous studies, we found lower absolute EMG amplitude values from the VL and RF during the MVICs in the older men compared with the younger men (Table ). These differences in EMG amplitude may have been due to an age‐related decrease in the amount of excitable muscle tissue .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies, we found lower absolute EMG amplitude values from the VL and RF during the MVICs in the older men compared with the younger men (Table ). These differences in EMG amplitude may have been due to an age‐related decrease in the amount of excitable muscle tissue .…”
Section: Discussionsupporting
confidence: 91%
“…Thus, surface EMG provides a global assessment of muscle activation and has been used to investigate age‐related differences in muscle activation . Several previous studies have demonstrated that the EMG amplitude is similar or lower in older compared with younger adults during a maximal voluntary isometric contraction (MVIC). The effect of aging on EMG amplitude during dynamic muscle actions is equally unclear, because several studies have demonstrated age‐related decreases in EMG amplitude, while others have shown no differences .…”
Section: Methodsmentioning
confidence: 99%
“…Changes in muscle strength and the electromyographic activity of the lower limbs are pronounced during the ageing process [17]. Such changes are especially dangerous for women with low bone mass [18].…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that differences between the upper and lower limbs are related to neuromuscular adaptations derived from greater activation of the upper limbs, as compared to the lower limbs. Therefore, exercises requiring more frequent activation of lower-limb muscles may be beneficial [17].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, as alterações musculares não se manifestam de forma homogênea em todos os grupos musculares dos membros superiores e inferiores durante o processo de envelhecimento. Estudos demonstram, sobretudo nas mulheres, maiores reduções na força dos membros inferiores (Amaral et al, 2014;Amaral, Castro, Doimo, Silva, & Novo Júnior, 2015).…”
Section: Introductionunclassified